Konflik Queensha Menghadapi Obsesi dalam Novel Because The Baby Karya Priska Safira - Mirya Anggrahini Nimpuno (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2018)
Because the baby is a novel written by priska savira. The novel tells about the experience of life of the main character named queensha.the purpose of this research is to identify queensha's love and obsession as the main character of the novel.library research is conducted in this study. In this research, the writer uses extrinsic theory includes obsession and sigmund freud's concept of id, ego, superego.the result of the research shows that queensha's obsession and conflict has affected her behavior that makes her feel hesitated.this condition brings her to a conflicts that happen with herself and external conflicts with other people